Can confounding by sociodemographic and behavioural factors explain the association between size at birth and blood pressure at age 50 in Sweden?. Issue 1 (February 1997) - Koupilová, I; Leon, D A; Vågerö, D
Abstract : STUDY OBJECTIVE: To evaluate whether socioeconomic confounding explains the relationship between size at birth and blood pressure at age 50. DESIGN: Cross sectional study with retrospectively collected data on size at birth. SETTING: Uppsala, Sweden. PARTICIPANTS: 1333 men born in 1920-24, and a subset of 615 men for analyses including early social circumstances. MAIN OUTCOME MEASURES: Blood pressure measured after 10 minutes rest in supine position. Crude and adjusted effect measures were compared. MAIN RESULTS: Controlling for sociodemographic characteristics at age 50, such as socioeconomic position, highest education achieved and marital status did not reduce the strength of the association between birth weight and systolic blood pressure at 50 years. In the total population, the slope of the body mass index adjusted relationship changed from -3.4 mmHg/kg to -3.5 mmHg/kg on additional adjustment for sociodemographic characteristics at age 50 (both p values < 0.01). Controlling for behavioural characteristics at age 50, such as smoking and recent alcohol drinking, did not affect the relationship between birth weight and blood pressure at 50. In the 615 men for whom information on sociodemographic circumstances in early life was available, adjustment for factors such as social class of the family, mother's marital status or area of residence, led to a slight reduction of the effect of birth weight on systolic blood pressure at age 50. The slope of the body mass index adjusted relationship changed from -2.8 mmHg/kg to -2.6 mmHg/kg after additional adjustment for early life circumstances in the sample as a whole (p values 0.09 and 0.12). Simultaneous adjustment for sociodemographic characteristics at birth together with sociodemographic and behavioural characteristics at age 50 led to only a slight reduction of the effect of birth weight on systolic blood pressure at 50 years. CONCLUSION: The strong inverse associations between birth weight and blood pressure among 50 year old Swedish men are highly unlikely to be explained by confounding with socioeconomic circumstances at birth or in adult life.